2022
DOI: 10.48550/arxiv.2203.09094
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Snowmass 2021 Accelerator Frontier White Paper: Near Term Applications driven by Advanced Accelerator Concepts

Abstract: While the long-term vision of the advanced accelerator community is aimed at addressing the challenges of future collider technology, it is critical that the community takes advantage of the opportunity to make large societal impact through its near-term applications. In turn, enabling robust applications strengthens the quality, control, and reliability of the underlying accelerator infrastructure. The white paper contributions that are solicited here will summarize the near-term applications ideas presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…With sufficient science motivation, one possible IEF that could be considered is a 20-100 GeV center-of-mass energy ANA-based linear lepton collider. In what follows we focus on the science case for an IEF since the necessary R&D effort as well as potential near term applications of ANAs are outlined in other white papers submitted to Snowmass21 [6][7][8]. The goal of the proposed IEF is to both carry out particle physics measurements in the 20-100 GeV ranges, as well as to serve as a ANA demonstrator facility.…”
Section: Jinst 19 T01010mentioning
confidence: 99%
See 1 more Smart Citation
“…With sufficient science motivation, one possible IEF that could be considered is a 20-100 GeV center-of-mass energy ANA-based linear lepton collider. In what follows we focus on the science case for an IEF since the necessary R&D effort as well as potential near term applications of ANAs are outlined in other white papers submitted to Snowmass21 [6][7][8]. The goal of the proposed IEF is to both carry out particle physics measurements in the 20-100 GeV ranges, as well as to serve as a ANA demonstrator facility.…”
Section: Jinst 19 T01010mentioning
confidence: 99%
“…Electron beams have been accelerated up to 8 GeV over 20 cm at the Lawrence Berkeley National Laboratory using a PW laser pulse propagating in a plasma channel [5]. A discussion of the status of ANA research as well as the necessary avenues for achieving progress in this field may be found in the whitepapers "Linear collider based on laser-plasma accelerators", "AWAKE, Plasma Wakefield Acceleration of Electron Bunches for Near and Long Term Particle Physics Applications", and "Near Term Applications driven by Advanced Accelerator Concepts" submitted to Snowmass21 [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A white paper highlighting the relevance of emerging applications driven by advanced accelerator concepts has been submitted to Snowmass21 [111]. Community outreach and discussions during the Snowmass process yielded a short list of relevant applications.…”
Section: Near-and Mid-term Applicationsmentioning
confidence: 99%
“…In particular, laser-wakefield accelerators (LWFAs), which are based on laser-plasma interactions, can produce high-brightness femtosecond electron bunches with low transverse emittance from a compact setup (for current state-of-the art parameters see table 1). However, some parameters of LWFA electron beams, such as transverse emittance, energy spread, laser-to-beam conversion efficiency or pulse repetition rate can be even further improved and more specifically tailored to their application, such as for future particle colliders [1] or laser-driven free-electron lasers (FELs) [2]. The specific properties of future particle colliders are determined by the requirements of future high-energy physics experiments, which are currently being evaluated.…”
Section: Introductionmentioning
confidence: 99%